FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELLITUS TIPE II DI WILAYAH KERJA PUSKESMAS SUNGAILIAT (JURNAL SMART ANKES, 2022)
Diabetes Mellitus is a methabolic diseases that market by increasing blood sugar due to distruption of insulin which functions as a hormone to maintain bodyhomeostasis by decreasing blood sugar levels. Base on data from Sungailiat Public Health center, cases of diabetes mellitus in 2018 were 530 (15,27%), in2019 were 708 (7,74%), in 2020 were 1360 (14,08%). This type of research used a cross sectional design, with a population of 1360 patiens who came fortreatment at the Sungailiat Health Center. Obtained a large sample of 103 respondents and sampling using purposive sampling technique. Data analysis usedUnivariate and Bivariate analysis with chi-square statistical test. The result showed that the factors related with the incidence of type II diabetes mellitus in theSungailiat Public Health Center working area in 2020 were heredity (p=0,000 POR 10,040), age (p=0,022 POR 3,031), obesity (p=0,002 POR 0,0212), physicalactivity (p=0,032 POR 2,867), and factors that are not related to the education variabel (p=1,000 POR 0,956). It is recommended for health workers at theSungailiat Health Center to routinely provide counseling and knowledge to people with diabetes mellitus in order to implement a healthy lifestyle to reduce riskfactors that may occur.